Beneficial Effects of Mixing Kentucky Bluegrass With Red Fescue via Plant-Soil Interactions in Black Soil of Northeast China - Xie, Fuchun; Zhang, Gaoyun; Zheng, Qianjiao; Liu, Kemeng; Yin, Xiujie; Sun, Xiaoyang; Saud, Shah; Shi, Zhenjie; Yuan, Runli; Deng, Wenjing; Zhang, Lu; Cui, Guowen; et al. (Frontiers in Microbiology, 2020)
Continuous monoculture of cool-season turfgrass causes soil degradation, and visual turf quality decline is a major concern in black soil regions of Northeast China. Turf mixtures can enhance turfgrass resistance to biotic and abiotic stresses and increase soil microbial diversity. Understanding mechanism by plant-soil interactions and changes of black soil microbial communities in turf mixture is beneficial to restoring the degradation of urbanized black soils and maintaining sustainable development of urban landscape ecology. In this study, based on the previous research of different sowing models, two schemes of turf monoculture and mixture were conducted in field plots during 2016–2018 in a black soil of Heilongjiang province of Northeast China. The mixture turf was established by mixing 50% Kentucky bluegrass “Midnight” (Poa pratensis L.) with 50% Red fescue “Frigg” (Festuca rubra L.); and the monoculture turf was established by sowing with pure Kentucky bluegrass. Turf performance, soil physiochemical properties, and microbial composition from rhizosphere were investigated. Soil microbial communities and abundance were analyzed by Illumina MiSeq sequencing and quantitative PCR methods. Results showed that turfgrass quality, turfgrass biomass, soil organic matter (SOM), urease, alkaline phosphatase, invertase, and catalase activities increased in PF mixture, but disease percentage and soil pH decreased. The microbial diversity was also significantly enhanced under turf mixture model. The microbial community compositions were significantly different between the two schemes. Turf mixtures obviously increased the abundances of Beauveria, Lysobacter, Chryseolinea, and Gemmatimonas spp., while remarkably reduced the abundances of Myrothecium and Epicoccum spp. Redundancy analysis showed that the compositions of bacteria and fungi were related to edaphic parameters, such as SOM, pH, and enzyme activities. Since the increasing of turf quality, biomass, and disease resistance were highly correlated with the changes of soil physiochemical parameters and microbial communities in turf mixture, which suggested that turf mixture with two species (i.e., Kentucky blue grass and Red fescue) changed soil microbial communities and enhanced visual turfgrass qualities through positive plant-soil interactions by soil biota.